Camaleão digital : o ensino remoto emergencial no Instituto Federal de Alagoas - Campus Piranhas - Santos, Marcos Vicente Miranda (2023)
The covid-19 pandemic accelerated the adoption of digital technologies in education, at the same time that teachers found themselves involved in different scenarios, evidenced by the gap between students who had basic structural conditions to face this period of crisis and others who had in school the opportunity to have the first meal of the day. The Piranhas campus of the Federal Institute of Alagoas is no different, as it welcomes students from public and private schools in the city and surrounding municipalities to students who completed their entire elementary education in the rural area, whether in courses integrated into high school, or in Youth and Adults, in addition to students entering higher education. The present study is part of the Technologies, Languages and Education research line, with the objective of analyzing institutional policies in the context of Emergency Remote Teaching at the Federal Institute of Alagoas implemented by teachers on the Piranhas campus during the period of the covid-19 pandemic. Thus, at first, this work uses studies that discuss: emergency remote teaching, Arruda (2020; 2021) Hodges et al. (2020), Silva (2020); studies dealing with digital and post-digital (BOA SORTE, 2020; CRAMER, 2014; CLAES THORE’N et al., 2019; SANTAELLA, 2016; STRIANO, 2019); discussions with official documents governing emergency remote teaching (BRASIL, 2020a, 2020b, 2020c, 2020d, 2020e, 2020f; IFAL, 2020); verticalization in Federal Institutes (SILVA; MELO, 2018; BONFANTE; SCHENKEL, 2020; OLIVEIRA; CRUZ 2017). Methodologically, this research presents a qualitative nature, characterized as a Case Study (YIN, 2010), with a procedure for collecting empirical data, having bibliographical and documental sources as information. Data collection was performed using questionnaires, analyzed from the perspective of Freeman's teaching research (1998). Participants are the teachers responsible for offering disciplines in courses integrated into high school, youth and adult education and higher education during Emergency Remote Teaching. I found that the professors faced many difficulties while adapting to Emergency Remote Teaching, which involved learning during teaching, health problems with changing routines and communication strategies with students through digital resources and the distribution of printed material.